1978
DOI: 10.1007/bf00121274
|View full text |Cite
|
Sign up to set email alerts
|

Performance models of undergraduate students on computer-assisted instruction in elementary logic

Abstract: Performance data were collected for students taking the computer-assisted instruction course in logic at Stanford University. The fit of the data to the Suppes, Zanotti, and Fletcher trajectory model was found to be good, though a systematic deviation from the model suggested some changes in the curriculum. A quantitative approach was used to pinpoint areas for curriculum revision. In addition, the model was evaluated for use as the basis of a predictive control mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Another test of the theory is provided by data from the Nicaragua Radio Mathematics Project (Searle et al, 1976) relating to the problem of optimizing review exercises within each 25-minute radio lesson, and within the approximately 150 lessons per school year. It is noteworthy that the predictions made by global models are not restricted to subjects of the elementary school, as indicated by application of the trajectory model to a university-level course on introduction to logic (Larsen et al, 1978). For investigators who seek to explore global predictions for optimizing various aspects of instruction and curriculum patterning, these models appear to have considerable usefulness.…”
Section: Karplus; Lawsonmentioning
confidence: 99%
“…Another test of the theory is provided by data from the Nicaragua Radio Mathematics Project (Searle et al, 1976) relating to the problem of optimizing review exercises within each 25-minute radio lesson, and within the approximately 150 lessons per school year. It is noteworthy that the predictions made by global models are not restricted to subjects of the elementary school, as indicated by application of the trajectory model to a university-level course on introduction to logic (Larsen et al, 1978). For investigators who seek to explore global predictions for optimizing various aspects of instruction and curriculum patterning, these models appear to have considerable usefulness.…”
Section: Karplus; Lawsonmentioning
confidence: 99%
“…Moreover, they showed that among students at all levels of achievement there are significant differences in the rates at which students move through the courses, demonstrating the importance of an adaptive curriculum sensitive to individual differences. A detailed examination of these points for students both at secondary school and university levels are given in Larsen, Markosian, and Suppes (1978) and Suppes, Fletcher, and Zanotti (1976).…”
Section: Introductionmentioning
confidence: 99%
“…We now present an approach to evaluation of curriculum that we have been developmg since the mid 1970s (the first article in the series is Suppes, Fletcher, and Zanotti, 1976). An extension of this work is to be found in Suppes, Macken, and Zanotti ( 1978), in Larsen, Markosian, and Suppes (1978), and in Malone, Suppes, Macken, Zanotti, and Kanerva (1979). The third of these articles (Larsen et af.…”
Section: Majectories: Theorymentioning
confidence: 79%